Instructor's resource manual for Starr/McMillan's Human biology, third edition - Sellers, Larry G.; Taylor, Jane B.; Feldcamp, Susan M.; Jackson, John D.; Lewis, Larry (Brooks/Cole Thomson Learning, 2001)
This teacher's resource manual, designed for use with Starr and McMillan's Human Biology (4th edition) textbook,includes chapter outlines, objectives, key terms, lecture outlines, suggestions for presenting the material, classroom and laboratory enrichment, ideas for classroom discussion, and sections on term paper topics, library activities, and special projects